Antropogeneza i jej związek z ewolucją wszechświata w teilhardyzmie - Grzegorz Baczewski (Studia Ecologiae et Bioethicae)
This paper deals with the connection between the origin of the human race and the evolving universe in the works of Teilhard de Chardin, the French thinker analysed this problem from different points of view: scientific, philosophical and theological, showing its different aspects.The results of his reflections on this topic form a system of thought in which Teilhard tried to explain the mystery of man and the universe, the main concept of this system is the evolution of the whole universe from a material into a spiritual reality. Part of this cosmic evolutionary process is also the origin of the human race (considered by Teilhard as a species of living creatures and only accidentally as individual human beings). Creation of the world and man according to Teilhard is also a continual process in which God uses the natural law of evolution. Man is the best part and the summit of this cosmic process, the human race has been craeted by God as one philum (monophiletism) and not as a couple (Adam and Eve in the garden of Eden) or many phila (poliphiletism). While creating human souls, God also uses the material elements of the world, sublimating them into spirit, these opinions created many problems for the Catholic Church and were not accepted. Teilhardian analyses of the future of the universe and mankind are very interesting and inspiring and have been used by many modern thinkers. Teilhard wrote about one global society united by science and technology (globalisation). In the future people will also form one sphere of human spirit, the sphere of common information (noosphere). Eschatologically, the whole universe along with the human race will be united with God as the mover and final cause of the cosmic evolution (its point Alpha and Omega).The end of the history of all created reality will be the transformation into spiritual reality of the Cosmic Christ, thus anthropogenesis will be fulfilled in cosmogenesis and finally in Christogenesis.